Marking Thought and Talk in New Testament Greek - Sim, Margaret G. (Havertown, United States : James Clarke & Co, 2011)
This book uses insights from a modern theory of communication, Relevance Theory, to examine the function of the particle i(/na [SET IN SpIonic] in New Testament Greek. It claims that the particle does not have a lexical meaning of ""in order that, "" contrary to accepted wisdom, but that it alerts the reader to expect an interpretation of the thought or attitude of the implied speaker or author. Evidence is adduced from pagan Greek and in particular the writings of Polybius, Dionysius of Halicarnassus, and Epictetus, as well as the New Testament. The implications of this claim give an opportuni.
4.3.3.4 CONCLUSION4.3.4 Authorial Choice in Same Context; 4.4 Examples from Literary Koine; 4.4.1 Examples from Dionysius of Halicarnassus; 4.4.2 Examples from Polybius; 4.4.3 Examples from Epictetus; 4.5 Summary; CHAPTER 5. Noun Clauses Introduced by hina; 5.1 Introduction; 5.2 Review of Metarepresentation; 5.3 Explication of a Noun, Adjective or Demonstrative; 5.3.1 Adjectives in Stative Clauses; 5.3.1.1 NEW TESTAMENT EXAMPLES; 5.3.1.2 EXAMPLES FROM THE DISCOURSES OF EPICTETUS; 5.3.2 Nouns and Demonstratives in Stative Clauses; 5.3.3 Nouns in Non-Stative Clauses Complemented by hina Clauses.
Print version record.
Added to collection customer.56279.3
Keywords: Bible. -- Language, style; Bible. -- New testament -- Criticism, interpretation, etc; Bible. -- New testament -- Translating; Greek language, Biblical -- Particles; Greek language, Biblical -- Context; Greek language, Biblical -- Particles; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Electronic books